Influence of chronic use of corticosteroids and calcineurin inhibitors on COVID-19 clinical outcomes: analysis of a nationwide registry. (March 2022) - Calderón-Parra, Jorge; Cuervas-Mons, Valentín; Moreno-Torres, Victor; Rubio-Rivas, Manuel; Blas, Paloma Agudo-de; Pinilla-Llorente, Blanca; Helguera-Amezua, Cristina; Jiménez-García, Nicolás; Pesqueira-Fontan, Paula-María; Méndez-Bailón, Manuel; Artero, Arturo; Gilabert, Noemí; et al.
Highlights: Chronic IS therapies entail different risk profiles and clinical outcomes in COVID-19 patients. Chronic corticosteroid use before admission confers higher mortality and risk of complications. Chronic calcineurin inhibitor treatment does not appear to have an effect on mortality. ABSTRACT: Objectives: The aim of this study was to analyze whether subgroups of immunosuppressive (IS) medications conferred different outcomes in COVID-19. Methods: The study involved a multicenter retrospective cohort of consecutive immunosuppressed patients (ISPs) hospitalized with COVID-19 from March to July, 2020. The primary outcome was in-hospital mortality. A propensity score-matched (PSM) model comparing ISP and non-ISP was planned, as well as specific PSM models comparing individual IS medications associated with mortality. Results: Out of 16 647 patients, 868 (5.2%) were on chronic IS therapy prior to admission and were considered ISPs. In the PSM model, ISPs had greater in-hospital mortality (OR 1.25, 95% CI 0.99–1.62), which was related to a worse outcome associated with chronic corticoids (OR 1.89, 95% CI 1.43–2.49). Other IS drugs had no repercussions with regard to mortality risk (including calcineurin inhibitors (CNI); OR 1.19, 95% CI 0.65–2.20). In the pre-planned specific PSM model involving patients on chronic IS treatment before admission, corticosteroids were associated with an increased risk of mortality (OR 2.34, 95% CI 1.43–3.82). Conclusions: Chronic IS therapies comprise a heterogeneous group of drugs with different risk profiles for severe COVID-19 and death. Chronic systemic corticosteroid therapy is associated with increased mortality. On the contrary, CNI and other IS treatments prior to admission do not seem to convey different outcomes.